RFID-GPS based mechanism using aodvrp for stolen vehicle detection in vanet - Varun Chand; Karthikeyan J (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The traffic on the road was in the rise for the past few years, with more and more vehicles enter the road there was less scope of having better traffic. However, it could be maintained with the implementation of the proper system. The other major concern was on the theft of the vehicles and the accidents the drivers succumb to while in the road. This paper recommends the novel RFID-GPS mechanism based on AODV Routing Protocol algorithm in the hybrid VANET configuration that was working as a decentralized Ad hoc. The algorithm was framed in such a manner that it could be effective in maintaining traffic through communication among Vehicles and vehicles (OBUs) to the Roadside Unit (RSU). The RSUs would generate the possible route by Ad hoc On-demand Distance vector routing protocol and control the signals within the accessible limit if there were an emergency. The information about the stolen vehicles and the driver would be sent to the police station and hospital respectively that aid to track the vehicle by the Radio Frequency Identification-Global Positioning System (GPS) information and save the driver in case of an accident. The performance of the RFID-GPS mechanism based on AODV algorithm based on VANET was analyzed in NS2 and is related to the existing Zigbee. The outcomes exhibited that the proposed method was better in all performance metrics especially in throughput.